World development indicators 2006 (Washington, D.C. World Bank, 2006)
Looking for accurate, up-to-date data on development issues? This indispensable statistical reference allows you to consult over 800 indicators for some 150 economies and 14 country groups in more than 80 tables. It provides a current overview of the most recent data available as well as important regional data and income group analysis in six thematic chapters: World View, People, Environment, Economy, States and Markets, and Global Links.
FRONT; TABLE OF CONTENTS; 1. WORLD VIEW; Text figures, tables, and boxes; Tables; 2. PEOPLE; 3. ENVIRONMENT; 4. ECONOMY; 5. STATES AND MARKETS; 6. GLOBAL LINKS; BACK.
Cover title.
Includes bibliographical references and index.
Keywords: Economic development -- Statistics; Economic indicators; Social indicators; Economic history; BUSINESS & ECONOMICS -- Urban & Regional; Developing countries -- Economic conditions -- Statistics; Electronic books